Feminism in Virginia Woolf essays: A Room of One’s Own and Three Guineas - Llamas Diéguez, Silvia; Zalbidea Paniagua, Maya (Journal of Artistic Creation and Literary Research, 2025)
This work aims to raise awareness about the subjugation that women had to endure during the nineteenth century and even nowadays. The main purpose of this work is to show how women fail to find their identity in a patriarchal world, being frustrated and having their own personal desires restrained, and how everything in our patriarchal society has collaborated to the aggravation of this identity crisis of women. It will also explore how this subjugation is analyzed in the literature of women writers, particularly in the works of the well-known feminist figure Virginia Woolf. The chosen works are A Room of One’s Own and Three Guineas. The last part will focus on analyzing how women can liberate from these patriarchal ideas that are rooted on their minds and how they can finally overcome gender inequality. This part will consider the important influence that women writers can have on other women, by giving voice to important feminist ideas through writing.